Pengaruh Pemberian Pupuk Organik KoHeA+MF Terhadap Produksi Benih Padi Junjuang Varietas Unggul Lokal - Wulantika, Trisia; Fitri, Febria; Ngakumalem, Ngakumalem; Sondang, Yun; Hardaningsih, Wiwik; Wahono, Sentot; Anty, Khazy (Perkumpulan Dosen Muda (PDM) Bengkulu, 2023)
Rice is a strategic food commodity whose production and productivity need to be increased to maintain the nation's food security.Seeds are one of the production inputs that have a significant contribution to the level of productivity.Therefore, various problems related to rice seed production must be addressed immediately. Problems related to fertilization can be solved by the application of organic fertilizer technology KoHeA +MF (organic fertilizer technology of chicken manure with bioactivator MOL banana poultry),this technology is a cost-effective and environmentally friendly technology.The research was conducted on the experimental land of the Payakumbuh State Agricultural Polytechnic, in June - October 2023.The research design was factorial arranged in a Randomized Group Design (RAK) with 3 replications. The first factor is the level of artificial fertilizer, namely A1: 0% NPK, A2: 25% NPK, A3: 50% NPK, A4: 75% NPK, A5: 100% NPK. The second factor is the dose of KoHeA+MF, D1: 0 tons ha-1; D2: 5 tons ha-1; D3: 10 tons ha-1, D4: 15 tons ha-1, D5: 20 tons ha-1 and D6: 25 tons ha-1.The experimental unit consisted of 90 experimental units. Data analysis using STAT program and DNMRT further test at 5% level. The results showed that the overall application of KoHeA+MF organic fertilizer and NPK inorganic fertilizer had a good effect on the growth and production of rice seeds. At the time of generative growth, KoHeA+MF organic fertilizer support the highest increase in the number of tillers at a dose of 10 tonsÂ ha-1 KoHeA+MF and 100 kgÂ ha-1NPK